PELATIHAN PEMASARAN BERBASIS ONLINE BAGI KALANGAN PEMUDA PRODUKTIF - Rena Feri Wijayanti; Joni Dwi Pribadi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
The purpose of Community Service is to improve the knowledge and capabilities in the field of marketing and applications especially making the blog in order to support online marketing as well as to create employment opportunities in the economic activities of the community in the form of improved economic conditions (income).The result: there are efficiencies in work, an increase in the primary revenue source trainee, work quality can be improved even more.